Sentencias de unificación jurisprudencial con fines de extensión de la jurisprudencia (años 2012-2014) (2017)
In the present work we sought to identify the Unification sentences issued by the Council of State that could be subject to jurisprudential extension, in accordance with established in articles 10, 102, 270 and 271 of law 1437 of 2011, ie specifically "Those that recognized rights in application of legal and constitutional rules" (Consultation and Civil Service Room of the Council of State, 2014, page 14), and which were handed down by the Council of State from July 2, 2012 to In 2014, as a basis for the above, in four chapters the concept and theory of judicial decision, judicial precedent and unification of jurisprudence were discussed, a parallel was made between the Judicial Precedent and the Jurisprudential Unification, later the latter two concepts were addressed as Sources Form of the Colombian Administrative Law, later to indicate the legal framework, the Development and Conte Xto Social of the Mechanism of Extension of Jurisprudence and its importance in the Social State of Law: In the light of the public service and the Right to Equality and in this way finally present the results obtained.